2022
DOI: 10.3390/en15093179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Biomass Supply Chains: The Case of the Canadian Wood Pellet Industry

Abstract: The ongoing COVID-19 pandemic has disrupted global economic activity in all sectors, including forest industries. Changes in demand for forest products in North America over the course of the pandemic have affected both primary processors and downstream industries reliant on residues, including wood pellet producers. Wood pellets have become an internationally traded good, mostly as a substitute for coal in electricity generation, with a significant proportion of the global supply coming from Canadian producer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…-term reduction in production capacity by sawmills. In other words, a demand reduction Gagnon et al (2022). found that production declines of wood pellets in Canada directly resulted from sawmill closures.…”
mentioning
confidence: 99%
“…-term reduction in production capacity by sawmills. In other words, a demand reduction Gagnon et al (2022). found that production declines of wood pellets in Canada directly resulted from sawmill closures.…”
mentioning
confidence: 99%